Interference and channel control techniques for the future of wireless communications - Tusha, Seda (İstanbul Medipol Üniversitesi Fen Bilimleri Enstitüsü, 2020)
Interference and random behavior of the propagation environment are the main impediments to serve a broad range of applications and use-cases in modern communication systems. Although conventional orthogonal multiple accessing (OMA) schemes are prominent for achieving high reliability, they are far from reaching the goals of 5G and beyond networks in terms of system capacity, massive connectivity, and latency. On the other hand, interest in high-frequency bands is growing due to the enormous amount of spare spectrum that has the potential to realize the aspirations of future communication systems. In addition to these considerations, next-generation communication systems require a flexible and scalable design to meet user equipment (UE) demands. For these reasons, this thesis study focuses on three pivotal research directions that control of interference in communication systems, control of channel randomness in millimeter wave (mmWave) bands, and the richness and flexibility of multidimensional signal transmission. In particular, non-orthogonal multiple accessing (NOMA) caused by partial and fully overlapping of the existing UEs, adaptive directional communication against low penetration capabilities in mmWave frequency band, and index modulation (IM)-aided multidimensional transmission for achieving flexibility are studied in the scope of this thesis. Despite all the efforts, having effective multiple access under non-orthogonal conditions is still a conundrum in the literature. As a promising approach, waveform domain NOMA concept is introduced for serving multiple users with different requirements. The goal of waveform domain NOMA is to control interference by means of unique waveform features and consequently ensuring the separability of the overlapped UEs at the receiver. Specifically, the control of interference distribution is provided via the coexistence of appropriate waveforms while the average power of the interference remains the same. Moreover, diversity gain is achieved through interference hopping during repetitions. Moreover, intercarrier-interference (ICI) control for asynchronous networks and inter-numerology interference (INI) control for OFDM systems with multi-numerologies are studied via the exploitation of frequency domain IM, i.e., OFDM-IM, with the design of novel subcarrier mapping schemes. Directional communication in mmWave bands provides opportunities to combat high-level propagation loss. However, initiating communication over a certain direction makes the link vulnerable against low penetration capabilities, i.e., blockage impact. Beamwidth optimization in mmWave frequency bands is proposed in order to combat high path loss and blockage impact. Lastly, IM-aided multidimensional communication opportunities are surveyed in a comprehensive manner. Specifically, a framework is developed for the purpose of efficient utilization of signal dimensions in order to address diverse requirements of 5G and beyond systems.

Girişim ve yayılma ortamının rastgele davranışı, modern iletişim sistemlerinin hedeflerine ulaşmak için temel engellerdir. Öte yandan, geniş uygulama yelpazisini bünyesinde barındırmak için yeni nesil haberleşme sistemlerinin esnek bir yapıya sahip olması gerekmektedir. Bu yüzden, mevcut kullanıcı ekipmanlarının (UE) kısmi ve tamamen çakışması kaynaklı dikey olmayan çoklu erişim (NOMA), mmWave frekans bandında düşük penetrasyon özelliklerine karşı adaptif yönlü iletişim, ve esneklik açısından çok boyutlu haberleşme imkanları bu tez kapsamında çalışılmıştır. Gelecek vaat eden bir yaklaşım olarak, farklı gereksinimleri olan birden fazla kullanıcıya hizmet vermek için dalga formu tabanlı NOMA konsepti tanıtılmıştır. Dalga formu tabanlı NOMA'nın amacı, benzersiz dalga formu özellikleri aracılığıyla paraziti kontrol etmek ve sonuç olarak alıcıda üst üste binen UE'lerin ayrılabilirliğini sağlamaktır. Özellikle, uygun dalga formlarının bir arada bulunmasıyla parazitin ortalama gücü aynı kalırken parazit dağılımının kontrolü sağlanmıştır. Milimetre (mmWave) dalga bantlarında yönlü iletişim, yüksek seviyeli yayılım kaybıyla mücadele etme fırsatları sunar. Ancak, belirli bir yönde iletişim, bağlantıyı düşük penetrasyon özelliklerine, yani tıkanma etkisine karşı savunmasız hale getirir. Yüksek yol kaybı ve tıkanma etkisi ile mücadele etmek için mmWave bantları için hüzme genişliği optimizasyonu önerilmiştir. Son olarak, indis modulasyonu (IM) tabanlı çok boyutlu iletişim fırsatları kapsamlı bir şekilde incelenmektedir. Özellikle, 5G ve ötesindeki sistemlerin farklı gereksinimlerini karşılamak için sinyal boyutlarının verimli bir şekilde kullanılması amacıyla bir çerçeve geliştirilmiştir.
Kablosuz haberleşmenin geleceği için girişim ve kanal kontrol teknikleri